Prevention of erectile dysfunction - Sign of a good prognosis after acute myocardial infarction - Dragana Stanojevic, D.; Apostolovic, S.; Jankovic-Tomasevic, R.; Salinger-Martinovic, S.; Kostic, T.; Djordjevic-Radojkovic, D.; Mitic, V.; Kurtovic, D.K.; Dakic, S. (European Journal of Preventive Cardiology, 2017)
Background: Erectile dysfunction (ED) is a predictor or marker of coronary artery disease in patients at high risk of cardiovascular diseases. The aim of our study was to investigate the prevalence of ED in patients with acute myocardial infarction (AMI) and after 2 years of follow-up, and to determine the association between ED and the concentrations of the markers of inflammation, endothelial dysfunction and oxidative stress which were measured on the third day after hospital admission. Methods: The study included 80 patients aged 62.25±10.47 years. The primary endpoints of interest were re-hospitalization due to cardiovascular causes and death during the 2 year period after hospitalization. The Sexual Health Inventory for Men (SHIM) was assessed at the point of hospital discharge and after 24 months. Results: 40.1% of patients had some degree of ED. The percentage of patients without ED increased (13.2%), while the percentage of patients with severe ED significantly decreased (14.7%) after 2 years. Patients with ED had significantly higher BNP levels [455.30 (387.75- 630.75) vs. 236.10 (162.60-400.60) pg/mL, p<0.05] and decreased levels of nitric-oxide [128.60 (115.50-149.60) vs. 156.80 (141.10-179.30) ±mol/L, p<0.05]. There was no difference in inflammatory markers between patients with/without ED. During the two years of followup, 9 patients died (6.5% without ED, 68.6% with ED) (X2 = 7.19, p = 0.015). During the same time period, 22 (27.5%) patients were re-hospitalized due to cardiovascular causes, of whom 59.1% had ED at hospital admission (p<0.05). Conclusions: Low levels of nitric-oxide were the best predictors of ED during AMI and after 2 years. ED predicted the worst outcomes of AMI: death and re-hospitalization. Lifestyle changes and nitric-oxide donors could help in the treatment of ED and in the improvement of the long-term prognosis for AMI.
Keywords: acute heart infarction; adult; cardiovascular system; death; endothelial dysfunction; erectile dysfunction; follow up; hospital admission; hospital discharge; hospital readmission; hospitalization; human; inflammation; lifestyle modification; major clinical study; male; middle aged; nitric oxide; nitric oxide donor; oxidative stress; prevalence; prevention; prognosis; sexual health